Circadian rhythmicity in substance use disorder male patients with and without comorbid depression under ambulatory and therapeutic community treatment - Antúnez-Vílchez, Juan Manuel; Capella, María del Mar; Navarro-Humanes, José Francisco; Adan, Ana (Taylor and Francis, 2016)
This study analyzes the circadian rhythmic profiles of patients with substance use disorder (SUD) and patients with comorbid major depressive disorder (SUD-MDD) under ambulatory and therapeutic community treatments. The sample included 40 men with SUD and 40 with SUD-MDD, with at least three months of abstinence. Participants completed interviews, a morningness scale, and wore an iButton® device to measure distal skin temperature over 48 hours. Results showed that all groups tended toward morningness, with no significant differences in sleep-wake schedules. SUD patients exhibited higher circadian rhythm amplitude and stability compared to SUD-MDD patients. Additionally, patients in therapeutic communities showed stronger circadian rhythms than those in ambulatory treatment. Overall, these findings suggest that SUD patients and those in therapeutic communities have better circadian functioning and alignment with the light-dark cycle, which may be indicative of treatment adherence and recovery status.
Keywords: Ritmos circadianos; Ambulatory treatment; circadian rhythm; circadian typology; distal skin temperature; dual diagnosis; major depressive disorder; substance use disorder; therapeutic community